The Reason of Code-Mixing in Livy Renata YouTube Videos - I Kadek Adika Grianata; Putu Desi Anggerina Hikmaharyanti (ELYSIAN JOURNAL : English Literature, Linguistics and Translation Studies, 2023)
Mixing language often occurs in many situations in the real life because languages always develop. Moreover, mixing language also can affect people life style. Due to this, code-mixing phenomenon found in Livy Renata YouTube channel needs to be investigated. The videos are on the special three days vlog namely Vlog day 1 Going to Semarang with Jefri Nichol, Prince, & Nopek, Vlog day 2 Grebek Kamar Nopek! Having dinner with Dikta & Nichol, Vlog day 3 BTS acting class! Back to Jakarta. This study focuseson analyzing the reason of code-mixing used by Livy Renata in her YouTube channel based on the theory from Hoffman (1991). Descriptive-qualitative method is used to analyze the data in this study. The steps of collecting the data include observation and note-taking techniques. The result of this study found only 5 reasons of code-mixing with the dominant reason used by the speakers is talking about particular topic.